Animal Welfare in the Conditions of Global Climate Change (AWCGCC) - (:unkn) unknown (Dnipro State Agrarian and Economic University, 2020)
The proceedings of the 1st International Scientific and Practical Conference "Animal Welfare in the Conditions of Global Climate Change" , which took place in Dnipro, April 21-22, 2020, are published in the collection. The information on the current problems in the following areas of research is given: Current issues of ecology and environmental protection; Mechanisms of living organisms adaptation to extreme conditions; Adaptive technologies and strategies under the global climate changes. The problems of environmental science, agricultural science and veterinary science are presented, modern ways of their solution are offered. The collection of materials will be useful for specialists in the field of ecology, biology, agriculture and veterinary medicine, as well as for applicants for educational degrees of Master and PhD. У збірнику опубліковано матеріали учасників І Міжнародної науково-практичної конференції «Добробут тварин в умовах глобальних змін клімату», яка відбулася у м. Дніпро 21-22 квітня 2020 року. Подано інформацію щодо сучасного стану проблем за такими напрямами досліджень: Актуальні проблеми екології та захисту довкілля; Механізми пристосування живих організмів до екстремальних умов; Адаптивні технології і стратегії в умовах глобальних кліматичних змін. Представлені нагальні проблеми науки про оточуюче середовище, сільськогосподарської науки та ветеринарії, запропоновано сучасні способи їх вирішення. Збірник матеріалів буде корисним для фахівців в галузі екології, біології, сільського господарства та ветеринарної медицини, а також для здобувачів освітнього ступеня магістр та доктор філософії.
Добробут тварин в умовах глобальних змін клімату (AWCGCC)
Keywords: adaptive strategies; адаптивні стратегії; ecological problems; екологічні проблеми; monitoring; моніторинг; climate changes; зміни клімату; animal welfare; добробут тварин